Mitochondria-Targeted SmsHSP24.1 Overexpression Stimulates Early Seedling Vigor and Stress Tolerance by Multi-Pathway Transcriptome-Reprogramming - Khatun, Muslima; Borphukan, Bhabesh; Alam, Iftekhar; Keya, Chaman Ara; Panditi, Varakumar; Khan, Haseena; Huq, Saaimatul; Reddy, Malireddy K.; Salimullah, Md. (Frontiers in Plant Science, 2021)
Among the diverse array of heat shock proteins across the three domains of life, mitochondria-targeted small heat shock proteins (sHSPs) are evolved in the plant lineage. However, they remained mysterious and understudied. In this study, we reported a systematic study of a novel mitochondria-targeted nuclear sHSP from eggplant (Solanum melongena L.; SmsHSP24.1). Differential expression of SmsHSP24.1 indicated its positive role exerted during stress conditions. Escherichia coli-BL21 cell line overexpressing the SmsHSP24.1 showed excellent thermo-tolerance ability, tolerating up to 52°C. Spectrometry and electron microscopy revealed a multimeric structure of the protein which acted as a molecular chaperone at high temperatures. Overexpression of SmsHSP24.1 significantly enhanced resistance against heat, drought, and salt stresses and showed rapid germination in constitutively overexpressed eggplant lines. RNA-seq analysis reveals an apparent upregulation of a set of reactive oxygen species (ROS) scavenging enzymes of the glutathione (GHS) pathway and mitochondrial electron transport chain (ETC). Significant upregulation was also observed in auxin biosynthesis and cell-wall remodeling transcripts in overexpressed lines. qPCR, biochemical and physiological analysis further aligned with the finding of transcriptome analysis and suggested an essential role of SmsHSP24.1 under various stress responses and positive physiological influence on the growth of eggplants. Therefore, this gene has immense potential in engineering stress-resilient crop plants.